PERAN INDONESIA DALAM RANTAI NILAI GLOBAL PRODUK ELEKTRONIK - Rizki Putri Nurdiati; Rina Oktaviani; Sahara Sahara (IPB University, 2015)
Globalization has transformed the structure of industry into global integration of socalled global value chains (GVCs). Some literatures suggest that electronic industry is known as a successful industry in establishing global value chain. Electronic industry is one of leading cluster in driving economic growth in Indonesia. This study aimed to analyze the role of Indonesia in electronic global value chain according to its share towards global electronic industry, linkages, and value added distribution. An input output analysis by using the Asian International Input Output Table 2005 was employed to analyze the share of each country in electronic global value chain, inter-sector linkages, value added, also output and income multiplier. The result showed that Indonesia had low participation in electronic global value chain. Indonesia’s output share was the lowest among all countries which resulted in low valueadded acquisition. Indonesia played the role as the input user from the various sectors. It is suggested that Indonesia electronic manufacture sector should be integrated with the input supplier sectors. Electronic computing equipment sector can be the main priority in enhancing Indonesia electronic manufacture sector since it has the biggest effect to economic growth. Keywords: electronic, global value chain, Indonesia, input output analysis